2013
DOI: 10.1007/s13142-013-0237-9
|View full text |Cite
|
Sign up to set email alerts
|

Translation and sustainability of an HIV prevention intervention in Lusaka, Zambia

Abstract: The scale-up of HIV treatment programs in sub-Saharan Africa necessitates creative solutions that do not further burden the health system to meet global initiatives in prevention and care. This study assessed the work environment and impact of providing a behavioral risk reduction intervention in six community health centers (CHCs) in Lusaka, Zambia; opportunities and challenges to long-term program sustainability were identified. CHC staff participants (n = 82) were assessed on perceived clinic burden, job sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Many studies have been conducted in low-and middle-income countries, most commonly in Africa (4,15,63,143). Such studies indicate the importance of strategic partnerships (89,112) and the impact of the broader social context and of health system weaknesses (15,63) as important influences on sustainability.…”
Section: Low-and Middle-income Countriesmentioning
confidence: 99%
“…Many studies have been conducted in low-and middle-income countries, most commonly in Africa (4,15,63,143). Such studies indicate the importance of strategic partnerships (89,112) and the impact of the broader social context and of health system weaknesses (15,63) as important influences on sustainability.…”
Section: Low-and Middle-income Countriesmentioning
confidence: 99%
“…Task-shifting has been used elsewhere in healthcare to address scaling problems (e.g., providing mental health services and HIV treatment in resource poor countries: Patel, Chowdhary, Rahman & Verdeli, 2011; Vamos et al, 2014), but had not been used previously with the BP or any similar program. Several studies supported task-shifting delivery of the BP (Becker et al, 2006; Becker, Bull, Schaumberg, Cauble, & Franco, 2008; Becker et al, 2010), with 8- and 14-month within-group effect sizes for ED risk factors and symptoms being similar in magnitude to those reported in the Stice et al (2006; 2008) trials using benchmarking (McFall, 1996).…”
Section: Addressing the Scalability Problem: Task-shifting To Peer-lementioning
confidence: 99%
“…Recordings were reviewed and rated using a checklist to evaluate the provision of key intervention elements in each of the sessions. Ratings indicated that in cohort 2, the first CHC led cohort, providers delivered 90% of intervention elements, and in cohorts 3 and 4, the CHC led and co-led cohort, providers delivered 75% of intervention elements [27]. Periodic visits and regular conference calls were held with all sites to guide strategies to enhance sustainability, and a refresher workshop was held yearly to enhance fidelity of intervention delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Meetings were held at each clinic with CHC Clinic Officers, Sisters in Charge and staff members to review Partner Project strategies and goals. Based on criteria outlined by the Partner Project regarding the duties associated with conducting the intervention [27], senior CHC staff selected those staff most appropriate for training as group leaders. Ongoing monthly meetings were conducted with Community Advisory Boards (CABs) at each clinic to facilitate community acceptance and uptake of the intervention across the duration of the study.…”
Section: Methodsmentioning
confidence: 99%